2014
DOI: 10.1262/jrd.2013-095
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms of Aberrant DNA Hypomethylation on the X Chromosome in Uterine Leiomyomas

Abstract: Abstract. We recently found that aberrant DNA hypomethylation is more common on the X chromosome than on other chromosomes in uterine leiomyomas by genome-wide DNA methylation profiling. To investigate the mechanism of aberrant hypomethylation on the X chromosome in uterine leiomyomas, we analyzed methylome and transcriptome data from three cases of leiomyomas and the adjacent myometrium. We found that eleven of the aberrantly hypomethylated genes on the X chromosome were common to the three cases. None of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…However, the expression of TSPYL2 was not upregulated in leiomyoma samples. 78 Leiomyomas are estrogen-dependent tumors. A growing body of evidence within the literature has investigated a link between the ER signaling and epigenetic regulation.…”
Section: Dna Methylation In Uterine Leiomyomamentioning
confidence: 99%
“…However, the expression of TSPYL2 was not upregulated in leiomyoma samples. 78 Leiomyomas are estrogen-dependent tumors. A growing body of evidence within the literature has investigated a link between the ER signaling and epigenetic regulation.…”
Section: Dna Methylation In Uterine Leiomyomamentioning
confidence: 99%
“…Remarkably, when the same regions were analysed on the samples of endometrial diseases, there were observed discrepancies, because the levels of methylation of these promoter regions did not correlate with the lack of ERα protein in human patient samples with endometrial disease. 89 Furthermore, in the study by Sato et al, 90 an aberrant hypomethylation within sequences of X chromosome including TSPYL2 gene has also been demonstrated. These changes were connected to higher expression of this gene in normal myometrium, whereas expression was not upregulated in case of leiomyomas.…”
Section: Epigenetic Background Of Tumourigenesis Of Leiomyomasmentioning
confidence: 92%
“…Bisulfite reactions were performed using an EpiTect Bisulfite Kit (Qiagen) with the following temperature conditions: 95 °C for 5 min, 65 °C for 85 min, 95 °C for 5 min and 65 °C for 175 min as previously reported [38]. The bisulfite-converted DNA was amplified by PCR using the primer pairs for ESR1 and ESR2 shown in Table 2 using the following thermocycling conditions: 95 °C for 10 min, and 40 cycles of 94 °C for 30 s, 60 °C for 30 s and 72 °C for 1 min followed by 10 min of final extension at 72 °C.…”
Section: Methodsmentioning
confidence: 99%